Evaluation of ventricular systolic dysfunction as a risk factor for acute kidney injury in intensive care unit - Ahmed Aly Obiedallah; Ashraf Anwar E. L. Shazly; Noura Gamal Nasr; Essam M. Abdel Aziz (SpringerOpen, 2021)
Abstract Background Heart failure (HF) is a major health problem. Cardiac and renal diseases interact in a complex bidirectional manner in both acute and chronic settings. Renal dysfunction in the setting of heart failure, termed the cardio renal syndrome (CRS), has been considered consequence of left ventricular dysfunction (LVD), whereby decreasing cardiac output (COP) results in renal under perfusion and consequent decreased glomerular filtration rate (GFR). Main body of the abstract This study showed that 500 patients were admitted to internal care unit (ICU), and out of them, 100 (20%) patients developed acute kidney injury (AKI) while 400 (80%) patients did not develop AKI. It is also showed that 67 (67%) of those with AKI and 100 (25%) of those with no-AKI had baseline ventricular systolic dysfunction, left ventricular dysfunction (LVD), right ventricular dysfunction (RVD), and biventricular dysfunction (BiVD)presented in 23 (23%), 16 (16%), and 28 (28%) patients of AKI group, respectively, and presented in 60 (15%), 30 (7.50%), and 10 (2.50%) patients, respectively, in patients without acute kidney injury (AKI) Short conclusion Our study revealed that AKI has highest incidence in patient with biventricular dysfunction followed by left ventricular dysfunction and lastly those with right ventricular dysfunction.